DIPLOMASI EKONOMI INDONESIA TERHADAP KOREA SELATAN DALAM INDONESIA-KOREA COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT (IK-CEPA) - Rizal Budi Santoso (Indonesian Association for International Relations, 2022)
This article aims to describe Indonesia's economic diplomacy towards South Korea through the Indonesia-Korea Comprehensive Economic Partnership Agreement (IK-CEPA) which seeks to provide equal benefits as part of balancing Indonesia's national interests. The qualitative approach and the theory of economic diplomacy proposed by Okano-Heijma are used. The results show that Indonesia's economic diplomacy process through IK-CEPA in an effort to increase the value of trade and investment between the two countries. However, after being agreed in 2021, this IK-CEPA cannot yet run because it still takes time for the ratification of the IK-CEPA cooperation.